Activated sludge mass reduction and biodegradability of the endogenous residues by digestion under different aerobic to anaerobic conditions: Comparison and modeling. (March 2016) - Martínez-García, C.G.; Fall, C.; Olguín, M.T.
Highlights: Modeling and comparing digestion rates in seven different aeration conditions. A model-sludge with only 2 fractions (the heterotrophs and its residues) was used. The endogenous residues biodegradation constant was estimated (0.001–0.004 d −1 ). Sludge reduction was faster in the 12 h–12 h (ON/OFF) intermittently aerated digester. Nitrif-denitrification activity and acid pH could be clues of the best performances. Abstract: This study was performed to identify suitable conditions for the in-situ reduction of excess sludge production by intercalated digesters in recycle-activated sludge (RAS) flow. The objective was to compare and model biological sludge mass reduction and the biodegradation of endogenous residues ( XP ) by digestion under hypoxic, aerobic, anaerobic, and five intermittent-aeration conditions. A mathematical model based on the heterotrophic endogenous decay constant ( bH ) and including the biodegradation of XP was used to fit the long-term data from the digesters to identify and estimate the parameters. Both the bH constant (0.02–0.05 d −1 ) and the endogenous residue biodegradation constant ( bP, 0.001–0.004 d −1 ) were determined across the different mediums. The digesters with intermittent aeration cycles of 12 h–12 h and 5 min–3 h (ON/OFF) were the fastest, compared to the aerobic reactor. The study provides a basis for rating RAS-digester volumes to avoid the accumulation of XP in aeration tanks.